Peter Shaffer's Amadeus - Abraham, F. Murray; Hulce, Tom 1953-; Zaentz, Saul; Forman, Milos; Mozart, Wolfgang Amadeus 1756-1791; Shaffer, Peter 1926- (The Saul Zaentz, 1984)
The film presents the life and music of Wolfgang Amadeus Mozart. Viewed through the memories of an envious rival, Antonio Salieri, a mediocre 18th century Viennese composer obsessed with and jealous of the musical genius of the age.